2018
DOI: 10.1038/s41598-018-25274-2
|View full text |Cite
|
Sign up to set email alerts
|

Different combination strategies for prophylaxis of venous thromboembolism in patients: A prospective multicenter randomized controlled study

Abstract: The aim was to evaluate the efficacy and safety of different combination strategies for prophylaxis of venous thromboembolism (VTE) after gynecologic surgery in patients at different levels of risk. This was a prospective multicenter randomized controlled study, in which 625 women who would undergo pelvic surgery for gynecologic diseases were stratified into three risk groups and then randomized into four groups to receive graduated compression stockings (GCS) alone (group A), GCS + low molecular weight hepari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 33 publications
0
49
0
1
Order By: Relevance
“…In an Asian study, an RCT of Chinese patients, the patients were randomized into four groups to receive graduated compression stockings (GCSs) alone (group A), GCS + LMWH (group B), GCS + IPCD (group C), and GCS + IPCD + LMWH (group D) [ 42 ]. The overall incidence of DVT was 5.1% [ 42 ]. Group A had the highest incidence of DVT (8.8%), followed by group C (5.2%), group B (3.8%), and group D (2.6%) [ 42 ].…”
Section: Statements Of Group 3: Pharmacological Venous Thromboembolism Prophylaxismentioning
confidence: 99%
“…In an Asian study, an RCT of Chinese patients, the patients were randomized into four groups to receive graduated compression stockings (GCSs) alone (group A), GCS + LMWH (group B), GCS + IPCD (group C), and GCS + IPCD + LMWH (group D) [ 42 ]. The overall incidence of DVT was 5.1% [ 42 ]. Group A had the highest incidence of DVT (8.8%), followed by group C (5.2%), group B (3.8%), and group D (2.6%) [ 42 ].…”
Section: Statements Of Group 3: Pharmacological Venous Thromboembolism Prophylaxismentioning
confidence: 99%
“…Importantly, a further 29 articles were excluded as they included patients at moderate or high-risk of HAT. 15 43 After full-text exclusions took place, a narrative synthesis was performed on a single article. 44 …”
Section: Resultsmentioning
confidence: 99%
“…There were 20 articles identified in the article screening process, which were subsequently excluded, consisting of moderate and high-risk surgical patients containing a single study arm assessing the use of GCS alone in the reduction of HAT. 19 , 21 – 23 , 25 30 , 32 35 , 37 40 , 42 , 43 All of the study arms consisted of patients using GCS without the addition of LMWH. The rate of HAT was as high as 59.2% in patients undergoing knee surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Combination of these strategies have been recommended by some for high risk DVT patients. 22 Warfarin sodium is an effective option for treating DVT, however dose adjustments based on INR have to be done. 23,24 Present study has similar results, as suggested by literature.…”
Section: Discussionmentioning
confidence: 99%